TEACHERS STRATEGIES IN TEACHING SPEAKING TO STUDENTS AT SECONDARY LEVEL - Khairuzzanila, Khairuzzanila (Fakultas Keguruan dan Ilmu Pendidikan Universitas Jabal Ghafur, 2021)
This study is aimed at portraying teacher’s strategies in teaching speaking to students at secondary level and recognizing students’ response towards the strategies by involving an English teacher and a class of 20 students. In the mean time, students’ response towards the strategies resulted in positive attitude as they responded that the strategies helped them to speak, as well as concerned oral production of students whose participation was emphasized. The purpose of this research is to find what strategies are suitable for use by teachers at secondary level. This research is a case study and uses qualitative methods. To obtain data, the authors conducted research for 3 days. The instruments used to collect data in this study were classroom observations, inrviews and questionnaire. It aims to find out strategies that are suitable for th teachers in teaching speaking to students at secondary level. The data shows that, a suitable strategy to be used by teachers in teaching speaking at secondary level in SMA Negeri 1 Peukan Pidie is improving student discussion and storytelling. By using strategy, teacher well be more easy in teaching and student easy to understand what the teacher well be given. Meanwhile, without strategy student well get bored and difficult to get the lesson. In the meantime, regarding the strategies used by the teacher, the overall result shows positive feedbacks on the strategies used by the teacher. it is evident that 40% students strongly agree, 20% students agree with the strategy used by their teacher and they are very interested in the strategy. and 40% of the students on the day I shared this question were absent.